Desirable and Usefulness Aspects Analysis of Web-based Data Portal using UX Honeycomb - Ika Nurlaili Isnainiyah; Ati Zaidiah; Yulnelly Yulnelly; Yuni Widiastiwi (STMIK Budi Darma, 2021)
The implementation of e-government in Indonesia, one of which is supported by Indonesia's involvement in the Open Government Partnership (OGP) in supporting the disclosure of public information. Satu Data Pandeglang web portal system is a manifestation of the implementation of e-government at the presence stage, where technology plays a role in providing basic information that is easily accessible to the public. This study aims to implement the user-centered design process by conducting an initial evaluation of the Satu Data Pandeglang web portal system based on two priority aspects of UX Honeycomb, namely the desirable and usefulness aspects. Based on the research results, the overall mean value of the eight variables from both desirable and usefulness aspects is 3.63 which is still below the value of 4. These results indicate that these two aspects of UX Honeycomb still need to be improved and redesigned at the next development stage